Mitigating chemotherapy-induced oral mucositis: a comparative trial of cryotherapy and normal saline - Salama, Heba; Abdelfattah, Eslam; Elkhodary, Tawfik; Soliman, Hanan (Jurnal Ners, 2025)
Introduction: Oral mucositis is one of the most prevalent and serious complications of chemotherapy that causes physical discomfort and impacts patients’ functional ability, emotional well-being, and quality of life. It can also delay treatment, prolong hospitalization, and contribute to psychological issues. This study aimed to compare the effects of cryotherapy and regular saline mouthwash on oral mucositis in cancer patients resulting from chemotherapy. Methods: A quasi-experimental study design was used, involving a sample of 64 cancer patients who were recruited from the Oncology Center at Mansoura University Hospital, Mansoura, Egypt, over 6 months. Two equal groups of thirty-two cancer patients each were randomly selected into study and control groups from the study population. This study used a single tool divided into two sections: demographic data, a health-related data sheet, and the World Health Organization (WHO) mucositis scale. The Monte Carlo exact test was used to obtain an accurate p-value. Results: Incidence of severe and moderate mucositis was lower in the cryotherapy group on the 21st day, where the p-value was 0.004. On the 7th- and 14th-day measurements, there were no statistical differences. Conclusions: The positive effect of cryotherapy on lowering chemotherapy-induced oral mucositis in cancer patients validated our research hypothesis.